Do anonymous job application procedures level the playing field? - Olof Åslund; Oskar Nordström Skans (Institute for Labour Market Policy Evaluation (IFAU), 2007)
Anonymous application procedures (AAP) are increasingly promoted as a way to combat employment discrimination. The idea gets support from theory and experimental evidence, but virtually nothing is known about its real-life effects. We present empirical evidence building on micro data collected in the Swedish city of Gothenburg, where AAP was used in parts of the local administration. Difference-in-differences estimates, with extensive controls for qualifications, suggest that AAP increased the chances of advancing to interviews for both women and individuals of non-Western origin. Women also experienced a higher probability of being offered a job, but no such effect is found for immigrants.
Keywords: J71; J78; 330; Anonymous applications; discrimination; employment; Arbeitsuche; Arbeitsmarktdiskriminierung; Frauen; Migranten; Einwanderung; Göteborg; Schweden